FAKTOR - FAKTOR YANG MEMENGARUHI KEBERHASILAN PENGOBATAN PADA PENDERITA TUBERKULOSIS PARU KASUS KAMBUH DI RUMAH SAKIT KHUSUS PARU MEDAN - AULIA RAHMI; ANCE ROSLINA (LP2MTBM MAKARIOZ, 2021)
Tuberculosis (TB) is a disease with a high mortality and mortality rate in Indonesia. Pulmonary tuberculosis relapsedcases are TB patients who were declared cured or treatment was completed by a doctor, but reported back to healthservices and now found sputum smear positive. The cause is Mycobacterium tuberculosis. Many things are risk factorsfor TB disease, including other individual factors (age, gender, occupation, etc.), home environment factors, habits,contact history and so on. Other factors are poverty, environment, crowds, and limited access to clean and healthylifestyles. In TB patients, the most important thing is adherence to taking anti-tuberculosis drugs so that resistancedoes not occur with someone appointed as a drug supervisor. In addition, side effects that often occur are red urine,nausea, weakness, vomiting, indigestion, joint pain, dizziness, itching of the skin, and tingling. This research is adescriptive study, with a case control study design. The frequency of patients with pulmonary tuberculosis cases basedon the level of adherence to OAT obtained as many as 15 people (46.9%) who lacked the level of compliance. Thenbased on the side effects of treatment, 13 people (40.6%). Then based on family support, there were 13 people(40.6%). Meanwhile, based on age, 16 people (50%) were most affected at the age of 36-45 years. Then based ongender, the highest in the research sample obtained was male with a total of 19 people (59.4%). Then based on thehistory of comorbidities where the most samples were those who did not have a history of disease as many as 21people (65.6%). Also based on occupation where the most are self-employed as many as 11 people (46.9%). Andlastly, based on the last education, the most affected by the last education were elementary school as many as 10people (31.3%). The effect of drug side effects, family support, and medication adherence affect the success oftreatment in relapsed pulmonary tuberculosis patients.